A critical comparison between dosage forms in traditional Persian pharmacy and those reported in current pharmaceutical sciences - M. Baranifard; M.M. Khazaei; S. Jamshidi; M.M. Zarshenas; A. Zargaran (Iranian Society of Pharmacognosy, 2017)
There were many natural pharmaceutical dosage forms cited by Persian pharmacists and physicians in the historical pharmacopeias (Qarabadins). This work aimed to perform a comprehensive study on "Qarābādin-e-Sālehi" (1765 A.D.), one of the main Persian pharmaceutical manuscripts defining traditional dosage forms. All traditional dosage forms as well as their definitions, descriptions and considerations were extracted by reviewing "Qarābādin-e-Sālehi". Then, the textbook of "Aulton's Pharmaceutics; the design and manufacture of medicines" was considered to compare the medieval knowledge of pharmaceutics with current ones. Overall, there were 226 different dosage forms which have been cited in traditional Persian pharmacy. Since many of them were related to the preparation method, the final list of dosage form was shortened to nearly 60 items including solid, semisolid, liquid and gaseous forms. On the other hand, almost 40 forms with oral, topical, nasal, parenteral, vaginal and rectal routes of administration are mentioned as current dosage forms. Some of the dosage forms are similar or as the same in traditional and current pharmacy. But, there were too many novel dosage forms in traditional Persian pharmacy. There were 11 types of traditional nasal forms whereas, this route is still known as a novel route of administration. Also 5 different ophthalmic dosage forms have been cited in the textbook. Many of traditional dosage forms were designed according to the medical purposes. Several current dosage forms have roots in the historical definitions and can be found in Persian medicine. However, there are forgotten traditional dosage forms which can be modified and optimized in pharmacy nowadays.